2016
DOI: 10.17140/aftnsoj-2-133
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Estimation of Glycemic Index of White Bread and Improvement of the Dietary Fiber

Abstract: Consumers of products preferably demand minimally processed products that do not contain chemical preservatives and maintain health benefits. These encourage the use of dietary fiber (DF) to combat some metabolic disorders like diabetes and other immunological compromisings. This study indicates the potential of DF to satisfy the lowering of estimated glycemic index from improved white bread. The sources were selected from crude fiber composition of different cereals and fruits. Fruits of ripen avocado mesocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This product contained twice as much fibre as traditional waffles, and it might have increased the time needed to digest the carbohydrates present in the dough. The influence of dietary fibre and fat on the reduction of glucose levels in blood was also investigated by Borczak and Taye [39,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This product contained twice as much fibre as traditional waffles, and it might have increased the time needed to digest the carbohydrates present in the dough. The influence of dietary fibre and fat on the reduction of glucose levels in blood was also investigated by Borczak and Taye [39,42].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison to the glycaemic responses recorded after consumption of bread and biscuits made form a traditional recipe with those modified by introducing a dietary fibre mixture (70% inulin, 20% guar gum, 5% glucomannan and 5% wheat fibre) to the applied flour, Marangoni and Poli [44] and Taye [42] demonstrated that the fibre-enriched products had a lower GI [42,44]. Our own research also showed that the replacement of wheat flour with wholegrain wheat flour resulted in an increase in the content of dietary fibre and total ash in the studied dishes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that affect starch digestibility include starch characteristics, enzyme inhibitors, amylose/amylopectin ratio, particle size of starch granule, processing method, starch gelatinisation, retrogradation and presence of other ingredients such as lipids, proteins and fibre [ 4 , 6 , 11 , 12 ]. Previous studies present persuasive evidence that certain dietary fibres noticeably reduced GI of foods, although the magnitude of GI reduction is dependent on the food type and processing involved [ 13 , 14 ]. Wheat (WB) and oat bran (OB) are cheap, easily accessible, fibre-rich food additives which, when incorporated into starchy foods, may reduce their GI.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of dietary fibres to amylolytic enzymes in the small intestine results in their transformation to short-chain fatty acids in the colon. These processes result in physiological benefits such as blood glucose regulation, laxative and prebiotic properties [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%